The use of herbal medicines in lactation: Perspectives of breastfeeding women and pharmacists - Sim, Tin Fei (Curtin University, 2014)
This study explored breastfeeding women and community pharmacists’ perspectives on herbal medicine use in breastfeeding. Stage 1 investigated prevalence and pattern of use of herbal medicines amongst breastfeeding women using a population-based survey. Stage 2 explored breastfeeding women’s experience of the use of herbal galactagogues and their perspectives on pharmacists’ roles. Stage 3 explored community pharmacists’ perspectives of their role in promoting safe and effective use of these medicines and supporting breastfeeding in the community.